Transfusion with Cryoprecipitate for Very Low Fibrinogen Levels Does Not Affect Bleeding or Survival in Critically Ill Cirrhosis Patients - Budnick, Isadore M.; Davis, Jessica P.E.; Sundararaghavan, Anirudh; Konkol, Samuel B.; Lau, Chelsea E.; Alsobrooks, James P.; Stotts, Matthew J.; Intagliata, Nicolas M.; Lisman, Ton; Northup, Patrick G. (Thrombosis and Haemostasis, 2021)
Background Fibrinogen (FIB) levels less than 150 mg/dL have been associated with increased rates of bleeding and lower survival in critically ill cirrhosis patients.Objective We aimed to determine if treatment with cryoprecipitate (CRYO) for low FIB levels is associated with bleeding outcomes or survival.Methods A total of 237 cirrhosis patients admitted to an intensive care unit at a tertiary care liver transplant center with initial FIB levels less than 150 mg/dL were retrospectively assessed for CRYO transfusion, bleeding events, and survival outcomes.Results The mean MELD score was 27.2 (95% confidence interval [CI]: 26.0–28.3) and CLIF-C acute on chronic liver failure score was 53.4 (51.9–54.8). Ninety-nine (41.8%) were admitted for acute bleeding and the remainder were admitted for nonbleeding illnesses. FIB level on admission correlated strongly with disease severity. After adjusting for disease severity, FIB on admission was not an independent predictor of 30-day survival (hazard ratio [HR]: 0.99, 95% CI: 0.99–1.01, p = 0.68). CRYO transfusion increased FIB levels but had no independent effect on mortality or bleeding complications (HR: 1.10, 95% CI: 0.72–1.70, p = 0.65).Conclusion In cirrhosis patients with critical illness, low FIB levels on presentation reflect severity of illness but are not independently associated with 30-day mortality. Treatment of low FIB with CRYO also does not affect survival or bleeding complications, suggesting FIB is an additional marker of severity of illness but is not itself a direct factor in the pathophysiology of bleeding in critically ill cirrhosis patients.
Keywords: transfusion; portal hypertension; gastrointestinal bleeding; disseminated intravascular coagulation; international normalized ratio